PERAN MODAL SOSIAL DALAM PEMBERDAYAAN INDUSTRI KERAJINAN DI PROVINSI BALI - Ni Nyoman Yuliarmi (PIRAMIDA, 2011)
The aims of this research determine : the effect of social capital on handicraftindustry empowerment. The population in this research are all SMEs actor atdistricts/county in Bali Province. To determine the sample, it is used purposivesampling method, based on the largest business units from their respective districts.The number of sample units represented by this population in each district is selectedby stratified random sampling method. The number of samples obtained at least 204people. This research uses quantitative analysis approach; the technique used isStructural Equation Modeling (SEM) using variance-based calculation process. Thecalculation is assisted by Partial Least Square (PLS), a SmartPLS software version2.0 M3.The research results showed that: Social capital is not proven able to affecthandicraft industry empowerment directly. The custom traditional institutions couldbecome mediating variable (full mediation) between social capital and the role ofgovernment towards the SMEs empowerment in Bali Province.